YouTube as a Medium for Expository Text Learning: The Perspective of Indonesian Language Teachers - Sihombing, Tuti Susianti; Rudy, Rudy; Syahfitri, Dian (Fitrah, 2025)
This study aims to determine the role of YouTube in improving expository writing skills: the perspective of Indonesian language teachers at SMA Negeri 1 Doloksanggul. The background of this study is that Indonesian language learning in the classroom often poses a challenge for teachers at school. This is because students' interest in learning Indonesian varies. Therefore, teachers utilize YouTube to improve students' skills in writing expository texts. This study employs a descriptive qualitative research method. Data is collected through written tests, observations, and interviews. The research subjects are Indonesian language teachers. Data validation is conducted using reference materials and member checks. The results indicate that the use of YouTube videos is viewed as a strategic approach that should be implemented in education for language skill development. Writing expository texts is quite difficult for students to do in learning. The use of YouTube is considered to attract students' attention because it can improve their argumentation skills, vocabulary, and understanding of expository text structure. The use of this media is also used as motivation for teachers and students at the high school level.